Free radical processes in rats tissues under influence of sodium hypochlorite and histamine - Bishko, O. I.; Holovchak, N. P.; Boyko, M. Y.; Sanagursky, D. I. (Biophysical Bulletin)
We investigated the action of histamine and of sodium hypochlorite on the organism. The object of research were lipid peroxidation processes in some tissues of rats and the aim was to find out the changing in intensity of lipid peroxidation under the actions of biogenic amine and sodium hypochlorite. In the selected samples we determined intensity of free-radical reactions by the content of the primary products of lipid peroxidation - hydroperoxides and secondary products - TBA-reactive substances. It was found that histamine interrupte the prooxidant state of the blood plasma, heart, liver and kidney. There were changes in the contents of hydroperoxides and TBA- reactive substances under the sodium hypochlorite influence on the background of histamine action. It was shown the increasing in the level of lipid peroxidation products of the intact animals, that consumpted the solution of sodium hypochlorite.